SOCIALIZATION OF STATE PROSECUTORS IN SOLVING CIVIL CASES OUTSIDE THE COURT IN THE WORKING AREA OF THE STATE PROSECUTORS OF CENTRAL ACEH - Adenan Sitepu (Asosiasi Dosen Perguruan Tinggi Islam, 2021)
The socialization activity for the duties of the state attorney general in the Takengon area. It is base on observations and interviews conducted with the public and government institutions, which show a common understanding of the prosecutor's duties in representing the state regarding the settlement of cases outside the court in the civil sector. Considering the large number of civil cases currently going to court and requiring a long time to wait for a decision, the non-litigation method of resolving cases is a very efficient and effective alternative when viewed from the benefits obtained. The purpose of restoring state finances can realize. The solution offered by the Datun team in overcoming these problems is to carry out socialization activities on the duties and functions of state attorneys in the non-litigation settlement mechanism to the public and government institutions.